The Implementation of Curriculum Policy at MAN Sibolga - Nurul Oktaviana Mekawati; Herianto Herianto; Syafaruddin Syafaruddin; Makmur Syukri (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Curriculum policy is an urgent matter that must be determined by the madrasa leadership every year. This is intended to upgrade components and learning activities in accordance with technological developments and community needs. This study aims to describe the implementation of curriculum policies at MAN Sibolga. The focus of this research discussion includes a study of the formulation, solutions, and steps for implementing curriculum policies at MAN Sibolga. This research method is a descriptive study with a qualitative approach. The data were obtained using observation, interview, and documentation techniques. Data analysis used data reduction techniques, data presentation, and verification, and was declared valid through triangulation techniques. The results of this study indicate that (1) The policy formulation process in developing the MAN Sibolga curriculum is in the form of carrying out deliberation activities or meetings. The meeting is in the form of deliberation or work meeting (work meeting), besides that seminars and discussions are held. In meetings and deliberation the head of madrasah held discussions to find formulations and solutions to determine a policy in building and directing MAN Sibolga; and (2) steps for implementing policies in curriculum implementation at MAN Sibolga by socializing to teachers and conducting training and guidance for teachers in understanding the curriculum so that it can be implemented properly.